2003
DOI: 10.1080/0892702031000117153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polydispersity and Thermal Exchange on the Flocculation Rate of O/W Emulsions

Abstract: According to recent simulations [Langmuir 16, 7975 (2000)], the flocculation rate (k f ) of concentrated oil in water (O/W) emulsions interacting through van der Waals forces, can reach values considerably higher than the one expected for a very dilute system of noninteracting spheres ð5:49 3 10 218 m 3 =sÞ: Similar calculations at a volume fraction f 5 0:001 using 64 particles only, already show a k f 5 5:83 3 10 218 m 3 =s; reasonably close to the theoretical prediction. In this report Brownian Dynamics (BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…During the past decade, there has been significant progress in the solution of some of the problems outlined above. Of all remaining limitations, the consideration of the coalescence mechanism in the case of deformable droplets is by far the most serious difficulty. The thinning of the film between large drops ( R i > 5 μm, where R i is the radius of the drop) involves at least six different steps. These include the formation of a dimple, the generation of a plane-parallel film, the appearance and enhancement of surface oscillations, and either the final coalescence of the drops or the formation of long lasting films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, there has been significant progress in the solution of some of the problems outlined above. Of all remaining limitations, the consideration of the coalescence mechanism in the case of deformable droplets is by far the most serious difficulty. The thinning of the film between large drops ( R i > 5 μm, where R i is the radius of the drop) involves at least six different steps. These include the formation of a dimple, the generation of a plane-parallel film, the appearance and enhancement of surface oscillations, and either the final coalescence of the drops or the formation of long lasting films.…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers, we used spherical nondeformable droplets in order to simulate the behavior of bitumen/water emulsions. Unlike solid particles, these drops coalesce as soon as their interfaces touch. Because drops are not deformable, there is no transition between primary minimum flocculation and coalescence.…”
Section: Introductionmentioning
confidence: 99%
“…The data of Figure 3 corresponds to system #12 in Refs. [ 19 , 73 ]. The surfactant concentration in the system ( C s = 10 −5 M) is not enough to prevent the coalescence of drops during the course of the simulation.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that fluctuations as high as 10,000 k B T must be allowed in order to reproduce a mean square displacement equal to: 〈 r 2 〉 = 6D Δ t. Cut off thresholds in the value of the deviates corresponding to kinetic energies of 1000 k B T and 100 k B T fail to reproduce the correct value of 〈 r 2 〉. It was evident that values of the displacement corresponding to the outskirts of the Gaussian distribution are necessary in order to simulate the Brownian movement of the particles correctly [ 19 ].…”
Section: Brownian Dynamics (Bd) Simulationsmentioning
confidence: 99%
“…Emulsion droplet size and distribution significantly influence its properties (Ambrosone et al 2004;Klink et al 2011;Whitby et al 2007;Urbina-Villalba et al 2003). It is well known that microfluidic devices are effective platforms for producing monodispersed microdroplets or microbubbles (Marmottant and Raven 2009;Choi et al 2010).…”
Section: Introductionmentioning
confidence: 99%